Efektivitas Website sebagai Media Pembelajaran Matematika Selama Masa Pembelajaran Daring - Susanti, Weni Dwi; Suripah, Suripah (Edumatica : Jurnal Pendidikan Matematika, 2021)
The Covid-19 pandemic caused learning activities to immediately stop and be diverted online. There are many obstacles faced by teachers and students. Therefore, it is necessary to choose the right learning media so that the learning process remains optimal. One media that can be used as a learning media is a website. This study aims to describe the effectiveness of the website as a media Â for learning mathematics during the online learning period. This type of research is descriptive quantitative with survey method. The sample in this study were 15 students of class VIII SMP Nurul Falah Pekanbaru who were selected by simple random sampling technique. Data obtained using google form which contains statements related to 5 aspects of website assessment, clarity of material, interactivity, accessibility, nature of efficiency, and effectiveness. The results obtained by the majority of students like the website as a medium for learning mathematics. The effectiveness of using the website was in the quite good category, 40% of students said the website was very effective, 53,3% said it was effective, and only 6,7% said it was ineffective. Based on this, the website becomes an effective learning medium to be used during the online learning period.